Knowledge spillovers and patent citations: Trends in geographic localization, 1976-2015 - Hyuk-Soo Kwon; Jihong Lee; Sokbae Lee; Ryungha Oh (Centre for Microdata Methods and Practice (cemmap), 2017)
This paper examines the trends in geographic localization of knowledge spillovers via patent citations, considering US patents from the period of 1976-2015. Despite accelerating globalization and widespread perception of the of distance," our multi-cohort -sample" study reveals significant and growing localization effects of knowledge spillovers at both intra- and international levels after the 1980s. We also develop a novel network index based on the notion of ," which an instrumental variable estimation shows to be a significant and sizable determinant of the observed trends at the state-sector level.
Keywords: C36; C81; O33; O34; O51; 330; Innovation; knowledge spillovers; patent citation; agglomeration; networkindex; farness